Additional Interventions to Enhance the Effectiveness of Individual Placement and Support: A Rapid Evidence Assessment. (22nd May 2012) - Boycott, Naomi; Schneider, Justine; McMurran, Mary
Abstract : Topic . Additional interventions used to enhance the effectiveness of individual placement and support (IPS). Aim . To establish whether additional interventions improve the vocational outcomes of IPS alone for people with severe mental illness. Method . A rapid evidence assessment of the literature was conducted for studies where behavioural or psychological interventions have been used to supplement standard IPS. Published and unpublished empirical studies of IPS with additional interventions were considered for inclusion. Conclusions . Six published studies were found which compared IPS alone to IPS plus a supplementary intervention. Of these, three used skills training and three used cognitive remediation. The contribution of each discrete intervention is difficult to establish. Some evidence suggests that work-related social skills and cognitive training are effective adjuncts, but this is an area where large RCTs are required to yield conclusive evidence.